AUGMENTED REALITY (AR) FLASHCARDS AS A TOOL TO IMPROVE RURAL LOW ABILITY STUDENTS’ VOCABULARY (Practitioner Research, 2019)
Issues concerning rural students’ low vocabulary and lack of interest and motivation to learn English have been widely researched, yet the use of technology as a teaching tool is scarce. The purpose of this Action research was to examine the effectiveness of using Augmented Reality (AR) flashcards on low ability rural students’ vocabulary. 10 Year 1 students were selected based on convenient sampling. Data were gathered using both qualitative and quantitative methods. Students’ pre-test, post-test scores, semi-structured interview and observation were used in gathering the data. Methodological triangulation was adopted to ensure trustworthiness of the data analysis. The results indicated that all 10 students’ vocabulary scores improved after being introduced to Augmented Reality (AR) flashcards. Results suggested that the Augmented Reality (AR) flashcards were effective in maintaining a high level of motivation and engagement among the students. Nonetheless, these findings provided useful insights towards the successful application of Augmented Reality (AR) in enhancing low proficiency students’ vocabulary.